Pengaruh Belanja Online terhadap Perilaku Konsumtif Pengguna Aplikasi Alfagift-Alfamart - Prasetyo Harisandi; Wiyarno Wiyarno (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Today's people need a way to shop that is easy and can save time and additional costs that can meet their daily needs. With the support and rapid development of the world of technology 4.0, the Alfagift shopping application owned by PT. Sumber Alfaria Trijaya Tbk for Alfamart retail stores is one of the answers to this problem by utilizing Android or IOS applications. From the existence of the application, it will lead to consumptive behavior in its use. This study aims to determine whether online shopping influences consumptive behavior in using the Alfagift application. This research method uses a quantitative approach by distributing questionnaires to 100 consumers as measured by a scale of 1-5, Smart PLS (partial least squares) is used in the analysis of this study to test external and internal models. The results of this study provide the result that online shopping has a significant effect on consumptive behavior. So that the Alfagift application can answer consumer questions and problems to simplify and increase daily shopping. People's consumptive behavior towards using online shopping applications, especially Alfagift, cannot be avoided without awareness in using these applications. Buying through online stores takes place without time and need. When buying online, one cannot estimate how intensive the purchase will be, in how many months and how many products will be purchased.